Residential buildings in workers' villages in Latvia in the 1940s and 1970s. Example of brick buildings in the Jelgava area - Ziemeļniece, Aija; Īle, Una (Landscape Architecture and Art, 2024)
With the change of political power in Latvia after the Second World War, the country’s economy changed. The devastation of the war and the post-war period in the 1940s-1970s brought a new character to Latvia’s outer suburbs with workers’ villages consisting of apartment buildings with root gardens, barns and cellars. The workers’ villages in the suburbs, as well as the centres of kolkhozes or sovkhozes in the rural areas, began to implement new types of housing projects in the post-war years. The buildings in the workers’ villages connected with industrial production (wood processing, brickworks, sand pits, peat mines, stone crushing plants, dolomite quarries, etc.) formed their own spatial structure. However, with the wave of collectivisation in the 1940s/1950s and the development of collective farm/sovkhoz centres (MTS or machine and tractor stations, creameries, horse rental centres, seed etching centres, gatherers, sugar beet reception centres, grain dryers, wool carders, etc.), the spatial structure of the built environment changed. The unifying aspect of the villages remained the subsistence farming character, where the residential area coexisted closely with the production area and the farm buildings - cattle sheds, pastures, hay sheds, wood shed, cellar, root garden, potato and fodder beet field. When the Latvian state’s economic policy changed in the 1990s, the transformation processes also affected the areas of the workers’ villages. Today, the character of post-war Soviet housing is still preserved and should be given the status of cultural heritage.